Propuesta de un manual de seguridad y salud ocupacional para el criadero de truchas “piscícola de los andes s.a” en la ciudad de Quito 2015 - 2016 - Cevallos González, Nancy Pricila (2016)
This research paper titled "PROPOSAL FOR A MANUAL OCCUPATIONAL SAFETY AND HEALTH FOR TROUT HATCHERY" Piscicola DE LOS ANDES SA "IN THE CITY OF QUITO 2015 - 2016. The overall objective, Offer and Safety Manual Occupational health for trout Hatchery Fish Farming Andes "Pisciandes" whose main business activity is the production and marketing of rainbow trout. The specific objectives of the research are to conduct a situational analysis regarding occupational safety of the company; identify, measure and evaluate risk factors that are exposed personnel working in the fish; Establish procedures to be used to adopt prevention measures and occupational health risks in the company and develop a plan of prevention of occupational risks Piscícola Company of the Andes. Also, this work has had its full theoretical support based on science, which has served to strengthen the information obtained; the methods used are: Scientific, being a guide for gathering information on the implementation of surveys, interviews and observation technique; Deductive methods applied during the investigation to analyze the information obtained during the collection of bibliographic information, whether records of the company or the like, as well as rules and regulations, so that conclusions obtained through general premises. Statistical method used for the interpretation of the data obtained during the survey of the operational and administrative part of the company Pisciandes. And finally the analytic-synthetic method served as support for the analysis of all the information obtained and thereafter reach the conclusions. The techniques used to collect data are set out below: Interview applied to the Production Manager of the company, to thereby obtain information to help us solve the problem, by identifying strengths and weaknesses of the company, in safety and occupational health. Observation used by visiting and reviewing the company premises. The Survey is applied in all 11 of these 8 correspond to the operators, one the lady in charge of food (cook); 1 to Contadora and over the Administrative Manager and Sales, through which could make the internal analysis of the company. Where was obtained among the following most important information: Interview and surveys can be applied as a fortress to rescue that was identified mainly the company if a budget designated for industrial safety, same as is used in the purchase of protective equipment. It is also noted that if there is interest by the company in the implementation of a system of safety management. It is noteworthy that all workers have social insurance and job stability as contracts are indefinite and 36% of workers have more than 8 years in the company. On the other hand during the interview, several weaknesses, such as were also identified: the company does not have political or industrial safety standards; on site there is no signage regarding industrial safety nor workers are trained on the subject, since 73% of workers have no knowledge on industrial safety, however 90% perceive the company if you are interested in safety of their workers. Finally, after having performed the data analysis and diagnosis of the current situation Pisciandes, by developing risk matrix main risks are identified, to be: mechanical, physical, chemical and psychosocial. Where the plan occupational safety and health was established as a central proposal, through the development of procedures and regulations to market one of the jobs, in order to safeguard the physical and mental integrity of each employee of the company. After the work developed and established the following conclusions: The company does not have a Manual Occupational Safety and Health; The company provides all employees the necessary protective equipment, although there is no control over the use thereof; also it notes that there is not enough signage for safety and occupational health; identified a very important strength is that all workers are insured (IESS), and have job stability. Regarding proposed the following recommendations: Implement a Plan Occupational Safety and Health proposed in this work, so that a safer environment for all those who are part of achieving this prestigious company Pisciandes; Use the support of institutions such as firefighters and police for various trainings and drills, so that timely and efficient response when an emergency guarantee is given. Raise awareness and implement a system of occupational safety is not something that is achieved in the overnight, it is a continuous work every day, is something to be constant up to the conscience of each worker, so it is recommended to be in continuous training and monitoring of the proposed activities